Efficient ion acceleration and dense electron–positron plasma creation in ultra-high intensity laser-solid interactions. (26th March 2018) - Del Sorbo, D; Blackman, D R; Capdessus, R; Small, K; Slade-Lowther, C; Luo, W; Duff, M J; Robinson, A P L; McKenna, P; Sheng, Z-M; Pasley, J; Ridgers, C P
Abstract: The radiation pressure of next generation ultra-high intensity (>10 23 W cm −2 ) lasers could efficiently accelerate ions to GeV energies. However, nonlinear quantum-electrodynamic effects play an important role in the interaction of these laser pulses with matter. Here we show that these effects may lead to the production of an extremely dense (∼10 24 cm −3 ) pair-plasma which absorbs the laser pulse consequently reducing the accelerated ion energy and laser to ion conversion efficiency by up to 30%–50% and 50%–65%, respectively. Thus we identify the regimes of laser-matter interaction, where either ions are efficiently accelerated to high energy or dense pair-plasmas are produced as a guide for future experiments.